2017
DOI: 10.5812/jjm.14378
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of lytB Gene for Detection of Streptococcus pneumoniae in Isolates and Clinical Specimens by Real-Time PCR

Abstract: Background: Streptococcus pneumoniae is a causative agent of morbidity and mortality worldwide. Diagnosis of pneumococcal infection includes conventional culture-based and molecular methods. Differentiation of S. pneumoniae from other mitis group streptococci is not reliable.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…The present study results revealed that the PNSP rate in IPD was 35.5%, of which 25.5% and 10% were PRSP (penicillin‐resistant S. pneumoniae ) and PISP (penicillin‐intermediate S. pneumoniae ), respectively. The findings of surveillance studies performed in Iran between the years 2014 and 2019 indicated that 20.8% and 58% of the studied isolates were PNSP 10,11,13,14,27,28 …”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…The present study results revealed that the PNSP rate in IPD was 35.5%, of which 25.5% and 10% were PRSP (penicillin‐resistant S. pneumoniae ) and PISP (penicillin‐intermediate S. pneumoniae ), respectively. The findings of surveillance studies performed in Iran between the years 2014 and 2019 indicated that 20.8% and 58% of the studied isolates were PNSP 10,11,13,14,27,28 …”
Section: Discussionmentioning
confidence: 96%
“…The findings of surveillance studies performed in Iran between the years 2014 and 2019 indicated that 20.8% and 58% of the studied isolates were PNSP. 10 , 11 , 13 , 14 , 27 , 28 Therefore, the prevalence of nonsusceptibility to penicillin emphasizes the necessity of continued monitoring of the pneumococcal population in Iran. The highest genetic diversity of pbp genes was found in the genetic profile of pbp2x , followed by pbp2b and pbp1a genes.…”
Section: Discussionmentioning
confidence: 99%
“…Molecular assays confirmed cultural and biochemical characterization of S. pneumoniae isolates. Isolates were examined for the presence of the lytB gene in DNA extracts by real-time PCR assay as previously described [13].…”
Section: Methodsmentioning
confidence: 99%